Sustentabilidade no design de embalagens de delivery: o papel do ensino - Marco, Isabella Gomes de (2021)
This dissertation organizes and describes Design perspectives and approaches that seek to advance design practices for the development of solutions that meet emerging needs in the contemporary world, and argues that the starting point is in education. Thus, the objective of this research was to identify how the teaching of Design can contribute to the sustainability of food delivery packaging, as these have increased in the pandemic scenario. To this end, it carried out an ex-post facto case study in the disciplines of Packaging Design and Design for Sustainability, in the Graphic Design course at the State University of Londrina, which were integrated and taught in the context of the COVID-19 pandemic. As a methodology, it sought bibliographic references on teaching Design, sustainability, food delivery packaging and urban solid waste. For the analysis of the subjects selected for study, the research adopted the phenomenological philosophical stance and inductive logic, as the predominance of the research is qualitative and sought to understand the variables that contributed to the analyzed data. The analysis carried out shows that the development of the disciplines sought to assimilate their teachings in the area of packaging creation with the environmental impacts caused by the pandemic caused by COVID-19 and the waste that disposable packaging caused in this period due to the increase in orders via delivery. According to the experience in teaching reported, it was possible to perceive that the insertion of a reflective thought around the environmental problem and Design, from a dialogic practice, allows a horizontal construction of attitudes that allow each individual to participate in the formation of the individual and collective knowledge. Taking into account the results of the effort to build socio-environmental values in a more democratic way, we can consider that the integration of disciplines brought an opportunity for the joint construction of principles such as autonomy, democracy and cooperation between educators and students, proven by projects with high quality of both the packaging itself and the service and strategic aspects of business, brand and positioning (SAMPAIO, 2021). Thus, as contributions, the research suggests the following ideas for the future of the disciplines: (i) the participation of a professional from the materials engineering area for the purpose of deepening; (ii) conducting the technical terms and tools of the D4S could have been presented in parallel to its phases; (iii) the exposure of content aimed at the intervention level of “proposing product-service systems”; (iv) implementation of a collaborative project between the entire class of the discipline, which could be organized based on the phases of the packaging's Life Cycle; (v) the adoption of Emotionally Durable Design (EDD) as a sustainable strategy.